Integration of the Experience-Based Approaches with the Early Phase Architectural Design Studios - Kararmaz, Omur; Ciravoglu, Aysen (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
As architectural design studios are the places where designing is learnt through experimenting designs, it forms the basic framework of the education of architecture. The early period of design studios, different from all other studios, are the courses in which the students experience and encounter designing for the first time; thus, the design-related skills and fundamental inclinations that are acquired in these studios influence the future designing actions of the students. In today's global designing environment wherein the boundaries between disciplines and boundaries are increasingly blurring, the design tools and approaches of different disciplines are frequently being used to develop opinions in research in order to develop the design process in the studios. In this regard, in the early period architecture design studios, before the architectural design stage, the studio education programs ensuring awareness of perception through experiencing the presently structured space are stipulated to increase the quality of students' spatial productions. Including the different experience studios, they experience the process of the design and they learn how to critically look at their environments, and they include the social components of architecture into their educations with regard to the participant architecture. In addition to the above stated acquisitions, the applications that are appended to the educational programs from similar other disciplines, such as installation, shall greatly contribute to students' production of collective information under headings such as the identity of space, becoming a part of a place, spatial approaches of different disciplines, and provisions of design elements within a space.
Keywords: Experimental design; architectural design education; studio; Architecture